Determinación de herramientas publicitarias digitales para internacionalizar la venta del ají charapita en una empresa privada, ciudad de Iquitos, Perú - Saavedra Lopez, Ambar Geraldine (2024)
The thesis "Determination of digital advertising tools to internationalize the sale of ají charapita in a private company, city of Iquitos, Peru.", the purpose is to know the possibilities of using certain tools that the company can use with the support of the internet to elaborate new digital advertising content with the aim of internationalizing the exportation of the product. The method of a qualitative investigation of a descriptive exploratory investigation was applied, the technique of structured observation and documental analysis of the company was used. It is a case study, por tanto, the population and sample are the same company. It studied the digital instruments of international SEO that the company uses, the content marketing, the e[1]commerce and the characteristics of the “ají charapita” product. It concludes with the need to open new virtual channels as a web site, the use of social networks, the elaboration of blogs, the use of Instagram, Google, E-mail marketing. Apply or use for content marketing, Mobile Marketing, E-mail Marketing and Inbound Marketing. In this way, the sales of the company can be improved, the national market share is increased, the profit margin is increased and the company can expand towards internationalization.